Do Corporate Social Responsibility Practices and Green Finance Dimensions Determine Environmental Performance? An Empirical Study on Bangladeshi Banking Institutions - Guang-Wen, Zheng; Siddik, Abu Bakkar (Frontiers in Environmental Science, 2022)
This study aims to examine the effects of Corporate Social Responsibility (CSR) and green finance dimensions on the environmental performance of banking institutions in a developing economy like Bangladesh. In order to identify the relationship between the study variables, primary data were collected from 388 employees of Private Commercial Banks (PCBs) in Bangladesh using a non-probabilistic convenience sampling method and analyzed using the Structural Equation Modeling (SEM) approach. The results suggested that CSR practices have a positive influence on the environmental performance. Furthermore, the results indicated that the social, economic and environmental aspects of green financing significantly influence the environmental performance of banking institutions. Overall, the paper concludes that CSR practices and financing of various eco-friendly projects play a crucial role in improving the environmental performance of organizations and ultimately promote a sustainable development in the country. Consequently, policy implications are discussed.